PERSEPSI WISATAWAN DOMESTIK TERHADAP EKSISTENSI PEKERJA FOTOGRAFER DI DAYA TARIK WISATA TANAH LOT - Pardiana, I Agus Yudi; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2016)
Workers photographers not only to sell their photographs, but also sells services to tourists with polite and friendly. Photographers try to make a good first impression for tourists to be willing to use their services. Photographers workers very existence needs to be improved, because it provides positive benefits. Types and Sources of data used is qualitative and quantitative, primary data and secondary data. Data collected by observation, interviews, questionnaires, literature, and documentation. Determination of mechanical informants using purposive sampling, sample collection techniques using analysis of compound interest and use acsidental sampling. The number of domestic tourists responses calculated using a Likert scale The existence of photographers at Tanah Lot tourist attraction really have a positive impact for tourist attraction and the local community. Because it can be an additional income.
Keywords: Existence, Photographer Services, and Perception.